2017
DOI: 10.1093/ejcts/ezx379
|View full text |Cite
|
Sign up to set email alerts
|

Inaccurate aortic stent graft deployment in the distal landing zone: incidence, reasons and consequences†

Abstract: Accurate stent graft implantation in the distal LZ with the currently available deployment mechanism is often challenging. An inaccurate landing is associated with a higher incidence of endoleak Ib.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
44
0
2

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 30 publications
(46 citation statements)
references
References 17 publications
0
44
0
2
Order By: Relevance
“…After the 23 full-text papers were read for eligibility, 10 additional studies were removed because eight studies did not include measurement of endograft position relative to an anatomical landmark or endograft apposition with the arterial vessel wall, one study measured these parameters from 2D digital subtraction angiography images, and one study reported measurements on fewer than 10 patients. The remaining 13 studies were included in this review [4][5][6][7][8][13][14][15][16][17][18][19][20]. A flowchart of the selection procedure is shown in Figure 1.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…After the 23 full-text papers were read for eligibility, 10 additional studies were removed because eight studies did not include measurement of endograft position relative to an anatomical landmark or endograft apposition with the arterial vessel wall, one study measured these parameters from 2D digital subtraction angiography images, and one study reported measurements on fewer than 10 patients. The remaining 13 studies were included in this review [4][5][6][7][8][13][14][15][16][17][18][19][20]. A flowchart of the selection procedure is shown in Figure 1.…”
Section: Resultsmentioning
confidence: 99%
“…Five studies assessed the endograft in the proximal landing zone in the aortic neck after EVAR [8,14,17,19,20], three studies assessed the distal landing zone in the common iliac arteries (CIAs) after EVAR [6,7,16], and three studies assessed proximal and distal landing zones [4,5,15]. One study assessed the proximal landing zone after TEVAR [13], and one assessed the distal landing zone after TEVAR [18].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Berezowski et al analysed the accuracy of landing in the distal landing zone in patients with a short distal landing zone. 2 Of 59 patients, they managed to deploy the stent graft accurately in the distal landing zone in just 10 (16.9%) patients. Precise landing was defined as a distance to the target vessel 5 mm.…”
mentioning
confidence: 99%